# How do you solve 3( x + 3) = 5- 2x?

Jun 23, 2018

See a solution process below:

#### Explanation:

First, expand the terms in parenthesis on the left side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:

$\textcolor{red}{3} \left(x + 3\right) = 5 - 2 x$

$\left(\textcolor{red}{3} \times x\right) + \left(\textcolor{red}{3} \times 3\right) = 5 - 2 x$

$3 x + 9 = 5 - 2 x$

Next, subtract $\textcolor{red}{9}$ and add $\textcolor{b l u e}{2 x}$ from each side of the equation to isolate the $x$ term while keeping the equation balanced:

$3 x + \textcolor{b l u e}{2 x} + 9 - \textcolor{red}{9} = 5 - \textcolor{red}{9} - 2 x + \textcolor{b l u e}{2 x}$

$\left(3 + \textcolor{b l u e}{2}\right) x + 0 = - 4 - 0$

$5 x = - 4$

Now, divide each side of the equation by $\textcolor{red}{5}$ to solve for $x$ while keeping the equation balanced:

$\frac{5 x}{\textcolor{red}{5}} = - \frac{4}{\textcolor{red}{5}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{5}}} x}{\cancel{\textcolor{red}{5}}} = - \frac{4}{5}$

$x = - \frac{4}{5}$